2012
DOI: 10.1016/j.molcel.2012.07.019
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Fkbp6 and the Chaperone Machinery in piRNA Amplification and Transposon Silencing

Abstract: Epigenetic silencing of transposons by Piwi-interacting RNAs (piRNAs) constitutes an RNA-based genome defense mechanism. Piwi endonuclease action amplifies the piRNA pool by generating new piRNAs from target transcripts by a poorly understood mechanism. Here, we identified mouse Fkbp6 as a factor in this biogenesis pathway delivering piRNAs to the Piwi protein Miwi2. Mice lacking Fkbp6 derepress LINE1 (L1) retrotransposon and display reduced DNA methylation due to deficient nuclear accumulation of Miwi2. Like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
134
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(140 citation statements)
references
References 44 publications
6
134
0
Order By: Relevance
“…For example, the Siwi-Ago3 chimera has N-PAZ of Siwi and MID-PIWI of Ago3. We first examined localization of the chimeric constructs, as the two Piwi proteins occupy different subcellular environments in BmN4 cells: Siwi is diffused in the cytoplasm, while Ago3 is enriched in perinuclear cytoplasmic granules called the nuage (Xiol et al 2012). Immunofluorescence studies indicate that the chimeric constructs follow the localization pattern of the protein contributing the N-PAZ domain, with HA-Siwi-Ago3 chimera being cytosolic and HA-Ago3-Siwi chimera localized to the nuage (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the Siwi-Ago3 chimera has N-PAZ of Siwi and MID-PIWI of Ago3. We first examined localization of the chimeric constructs, as the two Piwi proteins occupy different subcellular environments in BmN4 cells: Siwi is diffused in the cytoplasm, while Ago3 is enriched in perinuclear cytoplasmic granules called the nuage (Xiol et al 2012). Immunofluorescence studies indicate that the chimeric constructs follow the localization pattern of the protein contributing the N-PAZ domain, with HA-Siwi-Ago3 chimera being cytosolic and HA-Ago3-Siwi chimera localized to the nuage (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Total RNA extracted from Mov10l1 KI/− and Mov10l1 KI/KI testes was analyzed by qRT-PCR. Genomic locations of E18 Mili-bound piRNAs (Xiol et al 2012) and of the amplicons detected in this experiment are shown in Supplemental Figure S5C. to the piRNA 5 ′ ends. Fittingly, the shape of the relative coverage by MOV10L1 CLIP tags with respect to piRNAs (sharp leading edge with a long tail) (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6). Additional proteins, such as GASZ, Tdrds, and chaperones, are likely components of the pICL complex (Olivieri et al 2012;Preall et al 2012;Xiol et al 2012;Izumi et al 2013). MOV10L1 does not interact with Tdrkh (Saxe et al 2013), which is required for 3 ′ end maturation.…”
Section: Discussionmentioning
confidence: 99%
“…13,[21][22][23][24][25] However, the existence of only primary piRNAs, but not secondary piRNAs, in Drosophila ovarian somatic cells, and in pachytene spermatocytes and round spermatids in the murine testes, suggests that it may have other novel functions beyond TE suppression. 18,26,27 In mice, three PIWI family proteins have been identified, including MIWI (PIWIL1), MILI (PIWIL2), MIWI2 (PIWIL4), all of which are exclusively expressed in the testis. [28][29][30] MILI expression starts in primordial germ cells (PGCs) at embryonic day 12.5 (E12.5) and lasts until the round spermatid stage in adult testes, whereas MIWI2 is expressed only in PGCs in fetal testes and MIWI is exclusively present in the pachytene spermatocytes and round spermatids in postnatal testes.…”
mentioning
confidence: 99%
“…Indeed, global inactivation of each of the three PIWI proteins leads to differential phenotypes, which is consistent with the notion that the three have non-redundant functions despite the high degree of conservation in their domain structures. 22,27,31 Mili or Miwi2 global knockout male mice exhibit meiotic prophase I defects that are correlated with desuppression of LINEI and IAP retrotransposons, 20,32 whereas Miwi knockouts display a spermiogenic arrest in step-4 round spermatids, which is also associated with increased postmeiotic LINE1 activities. 9,29 Recently, Mili was conditionally inactivated in spermatogenic cells in postnatal testes and this study suggests that MILI and the piRNA pathway are required to posttranscriptionally silence L1 in pachytene spermatocytes even in the presence of normal L1 DNA methylation.…”
mentioning
confidence: 99%